A real-world drug safety surveillance study from the FAERS database of hepatocellular carcinoma patients receiving durvalumab in combination with tremelimumab - Cheng, Yang; Zhang, Mingji; Yao, Yi; Wang, Mingzuo; Xue, Zhong; Chen, Zhaoshuo; Zhang, Fan (Frontiers in Immunology, 2025)
ObjectiveDurvalumab plus tremelimumab has emerged as a key therapeutic option for unresectable hepatocellular carcinoma (HCC). This study aimed to meticulously monitor and identify its safety profile using real-world data from the Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsData were retrieved from the FAERS database for HCC patients who received durvalumab plus tremelimumab between the fourth quarter of 2017 and the fourth quarter of 2024. Significant adverse event (AE) signals were identified using the odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and mu-item gamma Poisson shrinker (MGPS). Time-to-onset (TTO) was analyzed using Kaplan-Meier method and Weibull modeling. Independent risk factors for drug-related mortality were determined via LASSO-Cox regression, and a risk prediction model was developed to assess prognostic value.ResultsDisproportionality signals were identified in 51 preferred terms (PTs) across 16 system organ classes. Notable PTs with strong signals included immune-mediated hepatic disorder, immune-mediated enterocolitis, and cytokine release syndrome. Several unexpected AEs were observed, such as thyrotoxic crisis and ulcerative colitis. Anaphylactic reaction emerged as an unexpected signal and was categorized by the European Medicines Agency as both a designated and important medical event. TTO analysis revealed that most AEs (63.21%) occurred within 30 days of administration, with a median TTO of 25 days. The occurrence of AEs was significantly influenced by age and AE type. Both exploratory LASSO-Cox regression analysis and risk prediction model preliminarily showed that immune thrombocytopenia, immune-mediated dermatitis, immune-mediated enterocolitis, immune-mediated myocarditis, multiple organ dysfunction syndrome, and myocarditis were independent risk factors for drug-related mortality.ConclusionThis pharmacovigilance study describes the safety profile of durvalumab plus tremelimumab in HCC. The findings may inform clinical monitoring strategies, though prospective studies are warranted for confirmation.